THE DEVICE OF THE ELECTRO-JIGSAW. EXPERIMENTAL STUDY OF THE CHARACTERISTICS OF THE ELECTRO-JIGSAW. - Kurnikov, K. D; Markov, A.M. (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2019)
Lobzik (from German Laubsäge) is a tool for curvilinear sawing of materials. Manual mechanical Jigsaw includes an arched frame with a handle and clamps for mounting the saw blade. The saw blade is thin and narrow, thanks to which it is possible to change the direction of sawing. The frame has a large clearance between the canvas and its top, so it can bypass the edges of the workpiece. Manual jigsaw is usually used for processing of wood and its derivatives (in particular, plywood), and also in jeweller practice for processing nonferrous metals. Electric Jigsaw is a hand-held power tool for sawing of various materials with reciprocating movement of saw blade (Fig. 1). The manual electric Jigsaw includes a hull with a flat platform at the bottom and a handle at the top. Inside is an electric motor and a mechanism that transforms the rotational motion of the engine shaft into the reciprocating movement of the guide. For fastening of cloths the shank with a clamping screw or a spring clamp is used.